A special gift for Grammy - George, Jean Craighead, 1919-2012 (Harper, 2013)
When Hunter collects a pile of stones that he leaves on his grandmother's porch, they are used by the neighbors for a myriad of purposes--and by Hunter to make a special necklace for his Grammy.